An ultrahigh-accuracy Miniature Dew Point Sensor based on an Integrated Photonics Platform - Tao, Jifang (2016)
The dew point is the temperature at which vapour begins to condense out of the gaseous phase. The deterministic relationship between the dew point and humidity is the basis for the industry-standard “chilled-mirror” dew point hygrometers used for highly accurate humidity measurements, which are essential for a broad range of industrial and metrological applications. However, these instruments have several limitations, such as high cost, large size and slow response. In this report, we demonstrate a compact, integrated photonic dew point sensor (DPS) that features high accuracy, a small footprint, and fast response. The fundamental component of this DPS is a partially exposed photonic micro-ring resonator, which serves two functions simultaneously: 1) sensing the condensed water droplets via evanescent fields and 2) functioning as a highly accurate, in situ temperature sensor based on the thermo-optic effect (TOE). This device virtually eliminates most of the temperature-related errors that affect conventional “chilled-mirror” hygrometers. Moreover, this DPS outperforms conventional “chilled-mirror” hygrometers with respect to size, cost and response time, paving the way for on-chip dew point detection and extension to applications for which the conventional technology is unsuitable because of size, cost, and other constraints.